Desymmetrization of meso-bisphosphates using copper catalysis and alkylzirconocene nucleophiles - Jacques, R; Pullin, R; Fletcher, S (Springer Nature, 2019)
A highly regio-, diastereo- and enantioselective Cu-catalyzed desymmetrization of diverse meso-bisphosphates with alkyl zirconium nucleophiles has been developed. The reaction tolerates functional groups incompatible with many common organometallic reagents and provides access to a broad range of functionalized carbo- and hetero-cyclic structures. The products bear up to three contiguous stereogenic centers, including quaternary centers and spirocyclic ring systems. In addition, application of the reaction conditions to C2-symmetric, racemic substrates revealed a rare Cu-catalyzed kinetic resolution.